(untitled) (Health Renaissance, 2014)
Cysticercosis is a parasitic infestation caused by cysticercus cellulose. Ocular and adnexal cysticercosis represents 13% to 46% of systemic disease. There are different modes of presentation of ocular cysticercosis. Case: Here we report a case with the left upper eyelid ptosis. On ocular examination, there was presence of a cystic yellowish mass of size of the eye ball in the upper palpebral sub-conjunctiva along with dystropia and limitation of extraocular movements in dextroelevation. Complete surgical excision of the cyst was achieved through splitting of the left upper eyelid. There was presence of sub-conjunctival cyst along with involvement of levator palpebral superioris (LPS) and superior rectus (SR) muscle. Histopathological examination of the cyst showed features suggestive of cysticercosis. The patient was symptomatically better postoperatively. He was commenced on oral prednisolone 1mg/kg and oral albendazole 400 mg for 28 days. Conclusion: Cysticercosis should be considered in cases of inflammatory swelling of subconjunctival space especially in people with poor personal and community hygiene. DOI: http://dx.doi.org/10.3126/hren.v11i3.9659 Health Renaissance 2013;11(3):293-296